Brand Awareness and Competitive Advantage among Beer Products in Kabale District, South Western Uganda - Moses, Agaba; Eliab Mpora, Byamukama; Eton, Marus (International Journal of Multidisciplinary and Current Educational Research, 2020)
In the current business environment firms are required to be more competitive and hostile. Brand Awareness is regarded as a very important concept in business because business organizations can use it to gain competitive advantage. Competitive advantage has been approached by looking at the external environment of the firm that is how the economic power of firms can be used to create competitive position in an industry. This study focuses on Resource Based View a model that provides a framework for identifying unique set of resources and this perspective shifts the approach of assessing competitive advantage from the external to the internal environment that is the resource power. This study, therefore, set out to determine the effect of brand awarenes on competitive advantage in beer products in Kabale district. The specific objective of the study was to (i) To determine the effect of brand awareness on competitive advantage in alcoholic beer products in Kabale district. The study used a descriptive survey research design. The target population was 1783 including wholesalers, retailers, customers and brand and marketing managers of Nile Special Lager, Eagle Lager, Senator Extra Lager, club and Bell beer products in the District of Kabale, South Western Uganda. Multistage sampling techniques were used in this study. Simple random sampling technique was used to select alcoholic beverages products and producers. Purposive sampling technique was adopted to sample shopping center to collect consumer information. Shopping centers were selected based on a marketing investigation. Primary data were used and collected using questionnaires. The descriptive analysis involving computing the mean, standard deviation, skewness, and kurtosis of the brand equity and competitive advantage variables, the inferential analysis was conducted using multiple regression analysis and the t-statistic and the p-value were adopted to test the hypotheses of the study. The study used the Statistical Package for Social Sciences (SPSS) as a tool to process and analyse data. The findings show that there is significant effect of brand awareness on competitive advantage. This research concludes that it is only when brand awareness is high it has a greater effect on competitive advantage in alcoholic beer products in Kabale district south. The study recommends that beer producers and brand managers should prioritize brand awareness constructs as their strategy to attract potential customers because it does show significant effect on competitive advantage. The study further recommends that beer producers should enhance their efforts to build brand awareness in order to achieve competitive advantage.The findings of this research provide knowledge on building and sustaining firm’s competitive advantange by deploying brand awareness as an intagible critical resource from customer point of view with specific implications for developing cost cutting marketing strategies to maintain firm’ competitive position in Kabale district, South Western Uganda.